Thermal requirements and impacts of chilling accumulation on the phenology of olive (Olea europaea L.) cultivars in Southern Brazil - Flávia Lourenço da Silva; Samuel Francisco Gobi; Vagner Brasil Costa; Flávio Gilberto Herter (Semina: Ciências Agrárias)
Chilling and thermal heat requirements play fundamental roles in the phenological cycle of olive trees (Olea europaea L.) by impacting the initiation of budburst, flowering, and productivity. In this study, we evaluated the thermal requirements of four olive cultivars, ‘Arbequina,’ ‘Koroneiki,’ ‘Picual,’ and ‘Arbosana,’ in the Campanha region of Rio Grande do Sul, Brazil, over eight phenological cycles (2015/2016 to 2023/2024). We determined the timing and duration of the budburst and flowering stages for these cultivars and also analyzed their chilling hour (CH), chilling unit (CU), and accumulated thermal sum (STa) requirements. The results revealed that chilling accumulation ranged from 136–419 CHs, whereas STa ranged from 61.50–161.40 °C.day⁻¹ for budburst and from 110.98–242.80 °C.day⁻¹ for flowering. Early cultivars, such as ‘Arbequina’ and ‘Koroneiki,’ exhibited lower chilling requirements and higher STa, whereas ‘Picual’ required greater chilling accumulation and lower STa. Principal component analysis revealed correlations between variables, demonstrating that mild winters anticipated phenological events. A negative correlation was observed between chilling and heat accumulation, and insufficient chilling compromised flowering synchrony, with potential effects on pollination and production. Early cultivars were more suited to mild winters than late cultivars, whereas late cultivars, e.g., ‘Picual,’ were more vulnerable to climate change. Our findings highlight the importance of adapting olive tree management to local conditions and choosing suitable cultivars to ensure adequate productivity in emerging subtropical regions.